Effects of CYP2D6 genetic polymorphism on the pharmacokinetics of metoclopramide - Bae, Jung-Woo; Oh, Kyung-Yul; Yoon, So-Jung; Shin, Hyo-Bin; Jung, Eui Hyun; Cho, Chang-Keun; Lim, Chang Woo; Kang, Pureum; Choi, Chang-Ik; Jang, Choon-Gon; Lee, Seok-Yong; Lee, Yun Jeong (Archives of pharmacal research, 2020)
Metoclopramide inhibits the central and peripheral D 2 receptors and is frequently prescribed in adults and children as an antiemetic or a prokinetic drug to control symptoms of upper gastrointestinal motor disorders. Metoclopramide is predominantly metabolized via N-dealkylation and it is primarily mediated by CYP2D6 which is highly polymorphic. Thus, the effects of CYP2D6 genetic polymorphism on the pharmacokinetics of metoclopramide were evaluated in this study. All volunteers were genotyped for CYP2D6 and divided into four different genotype groups ( CYP2D6*wt/*wt [ *wt = *1 or *2 ], CYP2D6*wt/*10 , CYP2D6*10/*10 , and CYP2D6*5/*10 ). Each subject received a single oral dose of metoclopramide 10 mg. Plasma concentrations of metoclopramide were measured by using HPLC-UV. Compared to CYP2D6*wt/*wt , AUC inf of CYP2D6*wt/*10 , CYP2D6*10/*10 , and CYP2D6*5/*10 significantly increased by 1.5-, 2.3-, and 2.5-fold, respectively. C max also increased significantly in comparison to CYP2D6*wt/*wt across all genotype groups, with 1.5-, 1.7-, and 1.7-fold increases seen in CYP2D6*wt/*10 , CYP2D6*10/*10 , and CYP2D6*5/*10 groups, respectively. The CL/F of metoclopramide decreased in CYP2D6 genotype groups with decreased function alleles, as decreases of 37%, 56% and 61% were observed in CYP2D6*wt/10 , *10/10 , and *5/*10 genotype groups in comparison to the CYP2D6*wt/*wt group. In conclusion, the genetic polymorphisms of CYP2D6 significantly affected metoclopramide pharmacokinetics.